"The Shape of the Wrath to Come": James Baldwin's Radicalism and the Evolution of His Thought on Israel. (29th September 2020) - Alahmed, Nadia
Abstract : This article traces the evolution of James Baldwin's discourse on the Arab–Israeli conflict as connected to his own evolution as a Black thinker, activist, and author. It creates a nuanced trajectory of the transformation of Baldwin's thought on the Arab–Israeli conflict and Black and Jewish relations in the U.S. This trajectory is created through the lens of Baldwin's relationship with some of the major radical Black movements and organizations of the twentieth century: Malcolm X, Elijah Muhammad and the Nation of Islam, and, finally, the Black Power movement, especially the Black Panther Party. Using Baldwin as an example, the article displays the Arab–Israeli conflict as a terrain Black radicals used to articulate their visions of the nature of Black oppression in the U.S., strategies of resistance, the meaning of Black liberation, and articulations of Black identity. It argues that the study of Baldwin's transformation from a supporter of the Zionist project of nation-building to an advocate of Palestinian rights and national aspirations reveals much about the ideological transformations of the larger Black liberation movement.